Thermoelasticity Coupling Transient Response of Composite-Material Direction Pipe - Jian-lin Zhong; Jie Ren; Da-wei Ma (Shock and Vibration)
Based on the positive scheme method, the thermal load of the jet flow in an inner composite-material direction pipe is obtained, and the thermoelasticity coupling transient response is investigated. The positive scheme method with second-order accuracy is extended for solving the axisymmetric Euler equations, and the supersonic axisymmetric jet flow over a missile afterbody containing jet exhaust is simulated. The correctness of the development for the positive scheme method is verified. With the developed positive scheme method used to simulate the jet flow in the inner direction pipe, the thermal load is obtained. The thermoelasticity coupling finite element model of the composite-material direction pipe is established, and the stress response under dynamic pressure, unsteady temperature, and coupling state is obtained. Results show that, at the beginning of engine ignition, the effect of dynamic pressure and temperature field on the coupling stress is basically the same, and after that, the contribution of the temperature field to the coupling stress increases, and the thermal stress is the main factor affecting the strength of the composite-material direction pipe.